Pengaruh Kepemilikan Asing, Tingkat Nasionalitas, Tingkat Perlindungan Investor, Lingkungan Hukum, dan Tarif Pajak terhadap Tax Avoidance Perusahaan Multinasional dengan Ukuran Perusahaan sebagai Variabel Moderasi - Ramadhona, Rizky Tri Nova; Susilowati, Nurdian (Business and Accounting Education Journal, 2023)
This research or study was conducted from previous research about what variable have influence on the tax avoidance because there is some research gap on many studies about tax avoidance. The aim of this research is to find out what variables can influence tax avoidance and whether company size is able to moderate tax avoidance behavior or not and also to examine the impact of the Covid-19 pandemic on tax avoidance in Indonesia. This research sample is a food & beverages multinational company in Indonesia and listed on Indonesia Stock Exchange. Using time period 2018-2022. Using a Stata 17 and the analysis for the data using regression analysis (OLS) with robustness test provided by the statistic application or Stata 17. The result from this research indicates that foreign ownership, nationality level, investor protection level, and tax rates doesn’t have influence on tax avoidance. On top of that, this research also indicate that firm size doesn’t give moderation to all independent variables on tax avoidance. However, this research giving indication that law environment able to influence tax avoidance in a negative way. This research gives information for an evaluation for the government and also for the company about tax managerial and planning.